The intergration of content and study in an EST programme - R. Subramaniam (Journal of Modern Languages)
The above discussion has highlighted some of the problems faced in an attempt to intergrate content and skills and the possible lines along which revision should proceed. The summative and formative evaluation procedures used to gauge student performance point to some gains in this direction. At best these materials could be viewed as an attempt to provide comprehensible input - be it for acquisition or learning to take place.